PENGEMBANGAN USAHA KECIL DAN MENENGAH (UKM) KUE SAGU BAGEA KHAS MANADO DI DESA LOPANA KECAMATAN AMURANG KABUPATEN MINAHASA SELATAN SULAWESI UTARA - Supriati, Arie; Lonto, Apeles Lexi; Rattu, Jan A. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
Abstract: This activity is a Community Partnership Program (PKM) which aims to develop small and medium-sized businesses (UKM) located in Lopana Village, East Amurang District, South Minahasa Regency, which develop businesses in the culinary field, typical Manado cakes, Bagea sago cakes. The UKM is UD.Minahasa which produces Manado typical Bagea Sago Cakes. The target achieved in this activity is to improve the quality and quantity of UD products. Minahasa was given an Electric Oven which previously used traditional combustion as well as local marketing and how to make packaging more attractive, so that it could be marketed better. In achieving this target, the result is a typical Manado bagea sago cake has a greater turnover because of the burning speed, packaging is more attractive and dares to enter the modern otlet and super market, thus the Manado bagea sago cake produced is expected to be of higher quality and increase.